Karakteristik Kaum Yahudi dalam Surat Al-Baqarah - Muslih Muslih (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2007)
The dynamics of the world have entered a new phase marked by the collapse of the Soviet Union. In the past, the Soviet Union was a superpower and a formidable adversary for the West, especially America. The new powder keg is Islam versus the West. The West is alleged to be dominated by Jews. Paul Findley, for example, mentions the formidable influence of Jews in America, affecting members of Congress and the Senate, as well as executives. Many presidents of that superpower are said to be rendered powerless, even kneeling under the pressure of lobbyists. This article will attempt to analyze various upheavals and imbalances caused by the hands of Zionist Jews throughout history.